MODERN TECHNOLOGIES FOR ASSESSING STUDENTS' SKILLS IN INTEGRATING CHEMICAL KNOWLEDGE WITH LIFE EXPERIENCE (International Conference on Modern Science and Scientific Studies, 2025)
In this article, it is noted that the development of adaptive synchronized criteria for assessing students' skills in integrating chemical knowledge with life experience into the application of modern technologies is one of the important directions of modern education and upbringing. Providing students with chemical knowledge and skills necessary for practical use in life situations based on a scientific and pedagogical approach is one of the main criteria for training personnel who meet the requirements of today.